2002
DOI: 10.1172/jci0215736
|View full text |Cite
|
Sign up to set email alerts
|

Selective parasympathetic innervation of subcutaneous and intra-abdominal fat — functional implications

Abstract: The wealth of clinical epidemiological data on the association between intra-abdominal fat accumulation and morbidity sharply contrasts with the paucity of knowledge about the determinants of fat distribution, which cannot be explained merely in terms of humoral factors. If it comes to neuronal control, until now, adipose tissue was reported to be innervated by the sympathetic nervous system only, known for its catabolic effect. We hypothesized the presence of a parasympathetic input stimulating anabolic proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
120
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 316 publications
(133 citation statements)
references
References 35 publications
11
120
0
2
Order By: Relevance
“…In addition, norepinephrine turnover is very low in WAT and BAT, as recorded in MSG-mice [40,41]. Although direct SNS controls fat tissue accumulation, rare evidences [42] exist which show direct effect of parasympathetic nervous system (PNS) on WAT and BAT metabolism. Nevertheless, the presence of PNS terminals on fat tissues has not been demonstrated [43].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, norepinephrine turnover is very low in WAT and BAT, as recorded in MSG-mice [40,41]. Although direct SNS controls fat tissue accumulation, rare evidences [42] exist which show direct effect of parasympathetic nervous system (PNS) on WAT and BAT metabolism. Nevertheless, the presence of PNS terminals on fat tissues has not been demonstrated [43].…”
Section: Discussionmentioning
confidence: 99%
“…Histamine also negatively regulates neutrophil infiltration via H2 receptors in allergic inflammation [76]. A very recent study has demonstrated that the vagus nerve innervates adipose tissue; the physiological impact of this innervation is associated with selective induction of endocrine function and leptin release [77]. Although the implication of leptin in chronic inflammation and rheumatoid diseases, respectively, remains controversial [78], a number of studies demonstrate a protective role for leptin in inflammation [79][80][81][82][83].…”
Section: Control Of Innate Immune Responses and Inflammation By The Ementioning
confidence: 99%
“…Retrograde tracing of white adipose tissue reveals a wealth of efferents originating at the DMV [77]. These efferents synapse on the M 1 muscarinic receptor on the adipocyte, which increases insulin sensitivity of the adipocyte.…”
Section: The Efferent Systemmentioning
confidence: 99%